The use of human keratinocytes for assessing the cytotoxicity and carcinogenic potential of chemicals and chemical mixtures - Bae, Dong-Soon, author; Yang, Raymond, advisor; Campain, Julie A., committee member; Fox, Michael H., committee member; Hanneman, William H., committee member; Mumtaz, Moiz, committee member (Colorado State University. Libraries, 2002)
From a public health perspective, exposure to single chemicals is seldom relevant. The problem of mixtures is extremely important because the rules governing their interactions and the consequent alterations of biological systems are directly related to toxic endpoints and public health. The mechanisms for chemical interactions are not well studied. To better understand the nature and biological significance of interactions in mixtures, we studied the acute cytotoxic and chronic carcinogenic effects of arsenic (As3-) alone or in a metal mixture that also included cadmium (Cd2+), chromium (Cr3+ and 6+). and lead (Pb2+) in human keratinocytes. The underlying goal of these studies is to determine the cytotoxic and potential carcinogenic effects of As alone and in an environmentally relevant metal mixture on human keratinocytes and to identify molecular markers for chemical carcinogenesis. Application of these biomarkers to assess the potential carcinogenicity of untested chemicals will be very useful and important to improve a current paradigm, the chronic animal bioassay, for chemical carcinogenicity testing. This objective is being met through meticulous cytotoxicity analyses of the metal mixture in four human keratinocyte strains utilizing a statistical additivity model, determination of the transforming potential of As and an As-containing metal mixture by the use of the immortal human epidermal keratinocyte (RHEK-1) transformation assay, and identification of a common suite of genes altered in 4 chemically-transformed malignant RHEK-1 cell lines utilizing DNA microarray and Real Time Reverse Transcription-Polymerase Chain Reaction (RT-PCR) technologies. The significant results of this research were: (1) As, Cr, Cd, and Pb in a mixture interact with each other to alter cytotoxicity in human keratinocytes in a dose- and cell strain-dependent manner; (2) these cytotoxic interactions may involve cellular defense mechanisms, as levels of glutathione and metallothioneins were substantially enhanced in mixture groups associated with antagonistic cytotoxic interactions; (3) chronic low level exposure of RHEK-1 cells to As alone or to a mixture containing As, Cr, Cd, and Pb inhibited spontaneous malignant conversion of this cell type. In contrast, a single treatment with 1-methyl-3-nitro-1-nitrosoguanidine (MNNG) enhanced neoplastic transformation; (4) utilization of cDNA microarray and Real Time RT-PCR methodologies demonstrated unique patterns of gene expression among 3 RHEK-1 cell populations treated with As, the metal mixture, or MNNG; (5) DNA microarray analyses on 4 chemically transformed RHEK-1 cell lines following exposure to 2 doses of MNNG, 4-nitroquinoline-l-oxide (NQO), or 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) identified a common battery of genes for potential molecular markers of the carcinogenic process, as well as chemical-specific alterations of gene expression. The utilization of human keratinocytes in this study highlights the potential for advancing alternative methods for assessing chemical cytotoxicity and carcinogenicity. Further gene expression analyses on phenotypically distinct stages (i.e., anchorage-dependent, anchorage-independent, morphologically transformed, tumorigenic) of RHEK-1 cells after chemical treatment will help us to correlate alterations in their expression with these stages and may identify early stage biomarkers for chemical carcinogenesis. The characterization of a causal relationship between chemical exposure and cancer may aid in the hazard identification step for risk assessment of other untested xenobiotics.
Keywords: environmental science; toxicology